Mary Douglas and anthropological modernism$h - Hendel, Ronald S. 1950- (2008)
Mary Douglas's scholarship has been described as “a classic expression of British anthropological modernism.” In this essay I explore the significance of her work within the larger intellectual horizons of modernism and within the Durkheimian tradition in anthropology. I then situate her work on the Hebrew Bible within this larger perspective, using her analysis of the abominable pig as an exemplary instance. Note: Readers of this article are encouraged to read first article 7 in this volume.
Keywords: Nachruf